In silico studies on modified hydroxamic acid and valporic acid as potential inhibitors for HDAC2 - Kandakatla, Naresh; Rathaur, Shikha; Sahoo, Smruti Sandhya; Ramakrishnan, Geetha (Bangladesh Journal of Pharmacology, 2013)
Histone deacetylases2, Class 1 HDAC family are emerged as an important therapeutic target for the treatment of various cancers. HDAC2 inhibitors are potent anti-cancer agents. Two inhibitors of HDAC2 are hydroxamic acid and valporic acid which are potent inducers of growth arrest, differentiation, and/or apoptotic cell death. Total 34 ligands optimized using triazole group substitution for the target protein Histone deacetylase2 on the basis of SAHA and valporic acid. All the ligands are docked with the target protein and results are compared with test compound SAHA. Eight ligands showed better binding affinity towards HDAC2.The binding affinity, free energy and drug scan screening of the above eight ligands have shown that P2, P6 and V6 molecules are best suitable to inhibit HDAC2.